How rich countries became rich and why poor countries remain poor: It's economic structure ... duh! - Jesus Felipe; Utsav Kumar; Arnelyn Abdon (Levy Economics Institute of Bard College, 2010)
Becoming a rich country requires the ability to produce and export commodities that embody certain characteristics. We classify 779 exported commodities according to two dimensions: (1) sophistication (measured by the income content of the products exported); and (2) connectivity to other products (a well-connected export basket is one that allows an easy jump to other potential exports). We identify 352 good products and 427 bad products. Based on this, we categorize 154 countries into four groups according to these two characteristics. There are 34 countries whose export basket contains a significant share of good products. We find 28 countries in a middle product trap. These are countries whose export baskets contain a significant share of products that are in the middle of the sophistication and connectivity spectra. We also find 17 countries that are in a middle-low product trap, and 75 countries that are in a difficult and precarious low product trap. These are countries whose export baskets contain a significant share of unsophisticated products that are poorly connected to other products. To escape this situation, these countries need to implement policies that would help them accumulate the capabilities needed to manufacture and export more sophisticated and better connected products.
Keywords: O14; O25; O57; 330; bad product; capabilities; low product trap; middle product trap; proximity; sophistication; structural transformation